LANGKAH PENTING GENERASI MILLENNIAL MENUJU KEBEBASAN FINANSIAL MELALUI INVESTASI - andreas rudiwantoro (Universitas Bina Sarana Informatika, 2018)
Abstract - Millennial generation are the genera-tion who are acquainted enough with the development of information technology. These generations has some characteristics i.e. creative, confidence and connected. Therefore, having the development of information technology today, this generation makes it as their life-style.However, some risks may become a hindrance for this generation if they focus too much on the development of information technology itself. In addition, they will automatically become aware of an adequate financial management. Thus, it is very essential for this generation to invest at a very younger age. It is to help them prepare for the future of financial freedom.Mutual funds and stocks are products of financial industry which can be a choice to invest for a couple of reasons. First, both of the products do not need such big financial capital to start off. Second, this can easily be done online. Investment should indeed be run with discipline, as well as by using idle funds that are allocated from the total of monthly incomeKeywords: Millennials Generation, Investment, Mutual Funds and Stocks. Abstrak – Generasi millenial adalah generasi yang cukup melek terhadap perkembangan teknologi info-rmasi. Generasi ini memiliki karakter creative, confidence dan connected. Kemajuan teknologi informasi menjadi gaya hidup mereka.Namun ada risiko yang menghadang bila generasi tersebut terlalu fokus terhadap perkembangan teknologi informasi, dan tidak memperdulikan mengenai pengelolaan keuangan yang memadai. Sangatlah perlu menyadarkan generasi millenial untuk berinvestasi sedini mungkin. Menyiapkan masa depan menuju kebebasan finansial. Reksadana dan saham adalah produk industri keuangan yang dapat dijadikan pilihan untuk berin-vestasi. Pertama karena ke dua produk tersebut tidak membutuhkan modal besar untuk memulainya. Kedua, Investasi reksadana dan saham, dapat dilakukan secara online. Investasi harus dijalankan secara berkelanjutan dengan mengunakan dana menganggur yang telah dialokasikan sebelumnya.Kata Kunci: Generasi Millenial, Investasi, Reksadana Dan Saham.